Efficient and secure multi-user outsourced image retrieval scheme with access control - Fuyuan SONG; Zheng QIN; Jixin ZHANG; Yu LIU (网络与信息安全学报)
In the cloud-based image retrieval services, the cloud server may not be fully trusted in which may arise privacy concerns.Some privacy-preserving image retrieval schemes have been proposed to protect image privacy.However, the traditional privacy-preserving image retrieval schemes have some weaknesses, such as inefficient and single-user setting.Therefore, an efficient and secure multi-user outsourced image retrieval (EMIR) scheme with access control was proposed.EMIR utilized matrix decomposition and proxy re-encryption to achieve multi-user outsourced image retrieval.By leveraging the techniques of one-time pad and matrix transformation, EMIR supported efficient and secure image retrieval based on Euclidean distance similarity in a privacy-preserving manner.In addition, EMIR applied locality sensitive hashing (LSH) to build searchable indexes in a privacy-preserving manner, which could improve the image retrieval performance.Specifically, a lightweight access control strategy by using role-based polynomial function was designed to authorize the legality of the query user.Security analysis shows that EMIR can protect the confidentiality of the images and the queries.The extensive experiments demonstrate that EMIR achieves efficient image retrieval.